MORPHOLOGICAL AND FUNCTIONAL CHANGES OF ERYTHROCYTES AND ENZYMES OF THE ANTIOXIDANT SYSTEM IN MULTIPLE SCLEROSIS - Churpiy, I.K.; Hryb, V.A.; Popel, S.L.; Liskevych, I.I.; Kuravska, Yu.S.; Hrynchak, V.I.; Pylypiv, L.A. (World of Medicine and Biology, 2024)
In the pathochemical complex formed in multiple sclerosis, the central role is given to the disintegration of metabolism, activation of lipid peroxidation processes, and suppression of the antioxidant defense system. The results of the conducted research indicate that in the pathogenesis of multiple sclerosis, significant importance is attributed to the activation of enzymatic and free radical lipid oxidation of erythrocyte cell membranes in conditions of complete or partial inability of antioxidant defense mechanisms. The consequence is significant changes in the structure of erythrocyte membranes and their functions. The detected destructive changes in erythrocytes correlate with the severity of clinical manifestations of multiple sclerosis, thus, they can be used not only to determine the severity of the disease but also for predicting its course, as well as monitoring the quality and effectiveness of therapeutic interventions in such patients.
Keywords: multiple sclerosis; antioxidant defense mechanisms; erythrocyte membranes